The Limitations and Unmet Needs of the Five Cornerstones to Guarantee Lifelong Optimization of Prophylaxis in Hemophilia Patients - Núñez, Ramiro; Álvarez-Román, María Teresa; Bonanad, Santiago; González-Porras, José Ramón; De La Corte-Rodriguez, Hortensia; Berrueco, Rubén; Jiménez-Yuste, Víctor (TH Open, 2022)
Prophylaxis to prevent bleeding is highly recommended for hemophilia patients. The development of new drugs and tools for modeling personalized prophylaxis provides the means for people with hemophilia to lead active lives with a quality of life comparable to that of nonhemophilic individuals. The choice of regimens must be made on a highly individual basis. Unfortunately, reference guides neither always concur in their recommendations nor provide directions to cover all possible scenarios. In this review, a group of experts identify the significant limitations and unmet needs of prophylaxis, taking advantage of their clinical experience in the disease, and supported by a rigorous literature update. To perform a more systematic and comprehensive search for gaps, the main cornerstones that influence decisions regarding prophylactic patterns were first identified.Bleeding phenotype, joint status, physical activity, pharmacokinetics/medication properties, and adherence to treatment were considered as the primary mainstays that should allow physicians guiding prophylaxis to secure the best outcomes. Several challenges identified within each of these topics require urgent attention and agreement. The scores to assess severity of bleeding are not reliable, and lead to no consensus definition of severe bleeding phenotype. The joint status is to be redefined in light of new, more efficient treatments with an agreement to establish one scale as the unique reference for joint health. Further discussion is needed to establish the appropriateness of high-intensity physical activities according to patient profiles, especially because sustaining trough factor levels within the safe range is not always warranted for long periods. Importantly, many physicians do not benefit from the advantages provided by the programs based on population pharmacokinetic models to guide individualized prophylaxis through more efficient and cost-saving strategies. Finally, ensuring correct adherence to long-term treatments may be time-consuming for practitioners, who often have to encourage patients and review complex questionnaires.In summary, we identify five cornerstones that influence prophylaxis and discuss the main conflicting concerns that challenge the proper long-term management of hemophilia. A consensus exercise is warranted to provide reliable guidelines and maximize benefit from recently developed tools that should notably improve patients' quality of life.
Keywords: hemophilia; prophylaxis; bleeding phenotype; joint status; physical activity; pharmacokinetics; treatment adherence